PENGARUH MEDIA PEMBELAJARAN TYPING MASTER DAN KEMANDIRIAN BELAJAR TERHADAP KETERAMPILAN MENGETIK SEPULUH JARI SISWA SMKN 25 JAKARTA - Muhammad Zein Pratama; Marsofiyati; Mayang Riyantie (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the effect of Typing Master learning media and self-directed learning on students’ ten-finger typing skills at SMKN 25 Jakarta. This research employed a quantitative approach with a causal associative design. The population consisted of 72 eleventh-grade Office Management students, all of whom were selected as the sample using a saturated sampling technique. Data were collected through questionnaires to measure Typing Master learning media and self-directed learning, as well as documentation of students’ ten-finger typing skill scores. Data analysis techniques included validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results reveal that Typing Master learning media has a positive and significant effect on ten-finger typing skills, self-directed learning also has a positive and significant effect, and both variables simultaneously have a significant effect on students’ typing skills. These findings indicate that interactive application-based learning media enhance the effectiveness of skill practice, while self-directed learning encourages consistency and intensity in students’ practice. The novelty of this study lies in the simultaneous examination of Typing Master learning media and self-directed learning within the vocational high school context. The implications of this study contribute to the development of technology-based learning and the strengthening of self-directed learning to improve students’ vocational skills.